Kepuasan Konsumen Produk Gula Semut Koperasi Semedo Manise Sejahtera Melalui E-Marketplace - Perwitasari, Lintang; Suyono, Suyono; Putri, Dindy Darmawati (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Tight competition in marketplace and increasingly consumers selective cause marketplace for more increase service and quality product their marketplace. This is must problem noticed by party company or UMKM for guard continuity his efforts in the future come. Study aim for analyze level satisfaction consumer and analyze performance attribute satisfaction important consumers for improved and repaired to fit with desire consumer. Method used is Customer Satisfaction Index (CSI) for know level satisfaction consumer and Importance Performance Analysis (IPA) for analyze performance attribute satisfaction important consumers for improved and repaired to fit with desire consumer. Data collection was carried out online with spread google forms to shopping customers online. Results study showing that Semedo Manise Sejahtera on the e-marketplace is 62.25 percent, which means enter in category satisfied, results CSI analysis too showing that still there is interest or hope customers who haven't can fulfilled by cooperative. The performance attribute of customer satisfaction of the Semedo Manise Sejahtera Cooperative, which are important for improvement are 11 attribute, while the performance of the attributes of the customer satisfaction of the palm sugar Semedo Manise Sejahtera Cooperative which is important to maintain because it is in accordance with the wishes of customers has as many as 9 attributes.